Exploring the proton transport mechanism of the mitochondrial ADP/ATP carrier: FA-cycling hypothesis and beyond - Pohl, Elena E; Vazdar, Mario; Kreiter, Jürgen (Protein science, 2025)
The mitochondrial ADP/ATP carrier (AAC, ANT), a member of the SLC25 family of solute carriers, plays a critical role in transporting purine nucleotides (ATP and ADP) as well as protons across the inner mitochondrial membrane. However, the precise mechanism and physiological significance of proton transport by ADP/ATP carrier remain unclear. Notably, the presence of uncouplers-such as long-chain fatty acids (FA) or artificial compounds like dinitrophenol (DNP)-is essential for this process. We explore two potential mechanisms that describe ADP/ATP carrier as either (i) a proton carrier that functions in the presence of FA or DNP, or (ii) an anion transporter (FA- or DNP). In the latter case, the proton is translocated by the neutral form of FA, which carries it from the matrix to the intermembrane space (FA-cycling hypothesis). Our recent results support this hypothesis. We describe a four-step mechanism for the "sliding" of the FA anion from the matrix to the mitochondrial intermembrane space and discuss a possible generalization of this mechanism to other SLC25 carriers.
Keywords: Mitochondria; adenosintrifosfát; mastné kyseliny; Biological Transport; bilayer lipid membranes; Fatty Acids; membrane proteins; 2,4-Dinitrophenol; protony; iontový transport; uncoupling protein; biologický transport; Animals; lidé; Mitochondrial ADP, ATP Translocases; Ion Transport; Protons; Humans; zvířata; reconstituted protein; mitochondriální ADP/ATP-translokasy; mitochondrial transporter; Adenosine Triphosphate; 2,4-dinitrofenol; MD simulations; mitochondrie